Photovoltaic technology for hot and arid environments - Aissa, Brahim; Tabet, Nouar (The Institution of Engineering and Technology, 2023)
The need to reduce greenhouse gas emissions and dependency on fossil fuels necessitates accelerated deployment of renewable energy, such as photovoltaics (PV). Regions with high insolation in the "Sun Belt" covering north Africa and the middle east, as well as in Australia, parts of Latin America, and elsewhere offer tremendous potential for PV, including for green hydrogen production. However, these regions are characterized by a hot climate and a dusty environment, both causing reduction of PV panel performance by 25% or more. The development of solar cells with enhanced resistance to thermal degradation and the reduction of panel soiling have therefore been subjects of intense study. Key developments include optimisation of the temperature coefficient of heterojunction solar cells, developing cells of higher open circuit voltage that are expected to show lower reduction of the panel efficiency at high temperatures, and analysis of soiling effects for better predictability and countermeasures. Based in part on research undertaken at Qatar Environment and Energy Research Institute (QEERI), and with contributions from chapter authors from a range of international institutions, this book addresses recent trends and developments in its field. Chapters revise solar energy resources and PV principles and thermodynamics, solar cell and module technology, bifacial solar cells, and soiling. A case study from Australia is followed by conclusions and future outlooks. "Photovoltaic Technology for Hot and Arid Environments" covers developments in the field for researchers and experts in industry and academia, and advanced students with an interest in the topic